2015
DOI: 10.3109/23744235.2015.1028099
|View full text |Cite
|
Sign up to set email alerts
|

An original case ofFrancisellatularensis subsp.holarcticabacteremia after a near-drowning accident

Abstract: We report the first case of Francisella tularensis subsp. holarctica bacteremia after water contamination in France. A 75-year-old man developed septic pneumonic tularemia after a near-drowning accident. We highlight the need for a longer incubation time for isolation of F. tularensis from blood cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…in water sources is likely given the existence of waterborne cases of tularemia [5][6][7][9][10][11] and the observed acquisition of F. tularensis subsp. holarctica (Type B) during the aquatic life cycle of the mosquito vector [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…in water sources is likely given the existence of waterborne cases of tularemia [5][6][7][9][10][11] and the observed acquisition of F. tularensis subsp. holarctica (Type B) during the aquatic life cycle of the mosquito vector [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…holarctica strain, a Type B biovar I, referred to as CHUGA-Ft6. This strain was isolated from a blood sample from a French patient suffering from a typhoidal form of tularaemia 19 . Interestingly, comparing FtFur to Fur from Escherichia coli (EcFur), Pseudomonas aeruginosa (PaFur), Legionella pneumophila (the agent of legionellosis, LpFur) and Yersinia pestis (the agent of plague, YpFur), we have evidenced that these proteins can be discriminated by their quaternary structure in solution 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the isolation of F. tularensis from the blood of infected patients has rarely been documented, possibly due to the poor sensitivity of blood culturing systems or the occurrence of bacteremia in the acute stages of infection ( Pittman et al, 1977 ). However, the number of reported tularemia bacteremia cases has increased with the use of improved blood culture isolation systems ( Reary and Klotz, 1988 ), and in recent years, more cases of tularemia bacteremia have been reported in the literature ( Haristoy et al, 2003 ; Sarria et al, 2003 ; Khoury et al, 2005 ; Fritzsch and Splettstoesser, 2010 ; Mohamed et al, 2012 ; Karagoz et al, 2013 ; Larssen et al, 2014 ; Nirkhiwale et al, 2015 ; Ughetto et al, 2015 ; Briere et al, 2016 ). Furthermore, studies have reported bacteremia in mice infected intranasally with F. tularensis LVS 48 h post-infection ( Chiavolini et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%